Calculation and Analysis of the Electric Field of the OIP Bushings under Internal Humidity and Surface Polluted Conditions using FEM - Mohammad Abouhosseini Darzi; Mohammad Mirzaie; Amir Abbas Shayegani Akmal; Ebrahim Rahimpour (Iranian Journal of Electrical and Electronic Engineering)
Bushings are one of the most important components of electrical equipment such as power transformers, reactors, capacitors. Most of the installed bushings have Oil-Immersed Paper (OIP) insulation structure. Bushing failure is caused by various reasons such as poor manufacturing process, overloading and also poor installation process, but moisture ingress is one of the main reasons of OIP bushing defect during its operation. In this paper, the electric field distribution of OIP bushings in multiple situations are simulated and effects of moisture distribution are analyzed. The simulations are stablished in polluted and clean surfaces of the studied bushing and done by COMSOL Multiphysics Software. The results show that non-uniform moisture distribution has a significant effect on electric fields of OIP insulation. This effect strongly increases with increasing the pollution on the external insulator of the bushing.